Evaluation of Janani-Sishu Suraksha Karyakram in a Community Development Block of Bankura District, West Bengal, India: A Mixed Methods Approach - Mitra, Satabdi; saha, Sanjay; Haldar, Dibakar; Sarkar, Aditya Prasad; Biswas, Daliya; Sarkar, Gautam Narayan (Indian Journal of Community Health, 2016)
Background: Government of India launched Janani-Sishu Suraksha Karyakram (JSSK) for cost-free care during pregnancy and infancy. Objectives: To assess awareness and utilization of JSSK services, estimate expenditures incurred to avail care and find out influencing factors for implementing JSSK. Methodology: A cross-sectional evaluation study using mixed methods was conducted during April-September 2015 in Gangajalghati block of Bankura district, West Bengal. From its thirty subcentres (lots), 120 mothers and pseudo-cohort of 120 infants were selected using Lot Quality Assurance Sampling. Beneficiary mothers and caregivers of infants were interviewed through house-to-house visits using semi-structured questionnaire. ANMs and ASHAs were selected by simple random sampling and involved in Focus Group Discussion. In-depth interview was conducted for Block Medical Officer of Health, Deputy CMOH-III of Bankura and Medical Superintendent cum Vice-Principal of BankuraSammilani Medical College and Hospital to explore factors of utilization. Result: Only 13.3% and 3.3% lots were acceptable for awareness and 16.7% and 13.3% for utilization for mothers and infants respectively. Overall coverage was 9.2% and 7.5% for awareness and 20.5% & 10.75% in utilization for services, while Out of Pocket Expenditure was estimated to be INR 690, 651 and 250, 545 (median, IQR) for mothers and infants respectively. Indirect costs were INR 540, 618 and 300, 460. Inadequate fund flow, manpower shortage, unavailability of referral transport timely, and poor prescribing for hospital supply medicines undermine the credibility of JSSK. Conclusion: Improved IEC and supervision, adequate fund and timely transport availability would forward this flagship programme of the Government.